A simpler method for total scalp irradiation: the multijaw‐size concave arc technique. (8th July 2014) - Inoue, Minoru; Konno, Masahiro; Ogawa, Hirofumi; Harada, Hideyuki; Asakura, Hirofumi; Fuji, Hiroshi; Murayama, Shigeyuki; Nishimura, Tetsuo
Abstract : The lateral electron‐photon technique (LEPT) and intensity‐modulated radiation therapy (IMRT) are commonly used for total scalp irradiation. However, the treatment planning and irradiation are laborious and time‐consuming. We herein present the multijaw‐size concave arc technique (MCAT) as a total scalp irradiation method that overcomes these problems. CT datasets for eight patients previously treated for angiosarcoma of the scalp were replanned using MCAT, LEPT, and IMRT. The MCAT was designed with a dynamic conformal arc for the total scalp, with a multileaf collimator to shield the brain. Two additional conformal arcs with a decreased upper‐jaw position of the first dynamic conformal arc were used to reduce the cranial hotspots. The prescribed dose was 40 Gy (2 Gy/fraction) to 95% of the planning target volume (PTV, defined as the total scalp plus a 4 mm margin). MCAT was compared with LEPT and IMRT with respect to the PTV dose homogeneity (D5%–95%), underdosage (V < 90%), overdosage (V > 110%), doses to the brain, and the delivery time and monitor units (MUs) for single irradiation. We were able to formulate treatment plans for all three techniques that could deliver the prescription dose in all patients. MCAT was significantly superior to LEPT with respect to PTV dose homogeneity, overdosage, and underdosage, although MCAT was inferior to IMRT with respect to dose homogeneity and overdosage. The mean brain dose and high‐dosage volume of all three techniques were low, but IMRT provided larger volume to the brain than did the other two techniques in the low dosage region. In MCAT, the mean delivery time could be reduced by approximately half or more, and the mean MUs could be reduced by at least 100 compared to the other two techniques. MCAT can achieve total scalp irradiation with substantially fewer MUs and a shorter delivery time than LEPT and IMRT. PACS number: 87.55.D‐